Do initial public offerings have an impact on company growth in Iceland? - Hilmar Andrésson 2002-; Magnús Yngvi Sigsteinsson 2002- (2024)
There has always been the question of when and how companies should raise capital. While there are various methods companies can choose from, initial public offerings continue to be the forefront in terms of corporate financing. The authors want to know if the decision to take a company public in Iceland will directly lead to growth in its operations and financials. The research consists of eight publicly traded companies in Iceland and eight privately owned companies within industries for comparison. In conclusion, the results are statistically insignificant and therefore no indication leading to the linkage between initial public offerings and the growth of firms in Iceland. The authors, however, express their concerns in the sample of firms available in Iceland, the results could therefore be skewed due to the small stock market here in Iceland. Thus, creating additional research opportunities by for example, adding the Nordic countries to the sample.